In Vitro Testing of Ciprofloxacin Formulations and Preliminary Study on BCS Biowaiver - Kyriacos, Soula Boustani (2009)
The purpose of this study was to compare the technical quality of ciprofloxacin tablets and examine the feasibility of biopharmaceutical classification system (BCS) biowaiver. Ciprofloxacin is a synthetic quinolone derivative anti-infective agent that has been classified as a Class 3 substance according to the biopharmaceutics classification system. Due to the importance of ciprofloxacin as an antibiotic for widely resistant bacteria and the importance of price in a community basis, different ciprofloxacin products available on the market were analyzed. The possibility of extending biowaivers to ciprofloxacin was also examined. Waiver for Class 2 and Class 3 drugs is sometimes scientifically justified. Ciprofloxacin has properties that are intermediate between BCS Classes 2 and 3, as the drug is highly soluble below pH 6 and poorly soluble above this pH. Ten generic brands and the innovator brand were compared on friability, hardness, average weight, content uniformity, disintegration and dissolution. In vitro testing indicates significant variations among some brands in terms of hardness, disintegration and dissolution. Dissolution testing met pharmacopeial requirements for all brands. However, significant variations in dissolution profiles were observed in 0.1N HCl and in phosphate buffer (pH 6.8) with no difference detected in acetate buffer (pH 4.5). The results suggest that the formulation and/or the manufacturing process affect the dissolution and thus the bioavailability of the drug products. The significance of the observed in vitro differences must be confirmed by an in vivo bioequivalence study.